Mortality from sepsis and complicated infections in the department of Santander, Colombia - Niño Mantilla, María Eugenia; Hormiga Sánchez, Claudia Milena; Ordóñez, Ivonne Tatiana; Villarreal Ibarra, Vivian Poleth; Ardila Acuña, Laura; Torres Dueñas, Diego (Universidad y Salud, 2014)
Introduction: The mortality associated with sepsis and complicated infections are not known in the department of Santander. Materials and methods: Mortality due to multiple causes related to sepsis and infections complicated was quantified. The data come from the DANE deaths database in 2008. Specific rates by age, sex and age-standardized mortality were calculated using the direct method. Results: In 2008, 9% of deaths were associated with sepsis, 1 in 10 deaths. ICD-10 codes related as underlying causes of sepsis are diverse but pneumonia, HIV virus disease and urinary tract infections are the most common in different age groups. The highest adjusted mortality was presented in men and in the extreme age groups. Conclusions: Sepsis is a public health problem in the department of Santander. This study provides a baseline for the evaluation of measures to reduce mortality from this disease.